Morphological studies on leaf epidermis in six species of Nekemias Raf. (Vitaceae) from China - Chu, Zhao-Fu; Meng, Ran; Meng, Ying; Song, Kun; Da, Liang-Jun; Nie, Ze-Long (Phytotaxa, 2024)
Nekemias Raf. (Vitaceae) is a re-defined genus isolated from the traditional Ampelopsis in the grape family of Vitaceae, including eight species mainly distributed in eastern Asia, and one in North America. In this study, the leaf epidermis of 28 samples representing six species of Nekemias and one species from the related genus of Ampelopsis are investigated using light microscopy. The results show that the shapes of leaf epidermal cells are polygonal or irregular. The variations of anticlinal walls are found commonly among species of Nekemia, especially within N. cantoniensis and N. grossedentata, which is probably associated with their habitats. Irregular stomata are found on the abaxial surface. The epidermal hair styles are multicellular, single-row on both sides and common in N. cantoniensis, N. grossedentata, and N. rubifolia, not in N. chaffanjonii and N. hypoglauca. Our results highlight that the variation of leaf epidermis in Nekemias are possibly related to the environment and habitats.